NANOPARTICLE FOR SUSTAIN RELEASE OF ACYCLOVIR INVITRO AND INVIVO DRUG COMPARTMENT MODELLING - Kushwah, Mahendra Singh Kushwah (International Journal of Multidisciplinary Research and Studies, 2021)
The main objective of this study was to organize the In-Vitro and In-Vivo correlation of immediate release Acyclovir tablets of 800 mg. In vitro and in vivo studies are done on the test product as Acyclovir Tablet USP 800 mg (containing Acyclovir 800 mg) of Cadila Medicinal Ltd., India versus Zovirax Tablet 800 mg (containing Acyclovir 800 mg) of GlaxoSmithKline, USA. In vivo studies are done in 36 healthy, adult, mortal subjects under fasting conditions. In vitro dissolution study was done using USP outfit II at 50 rpm in0.1 N HCL for 45 twinkles. The in vitro – in vivo interdependence of Acyclovir shows an R- squared value of0.9794 in the excel worksheet, which depicts a successful correlation between in vitro and in vivo characteristics of the medicine. In addition, PE AUC and PE C-max were planted to be –4.604 and-11.19 independently for each expression. The present study shows a good correlation between in vivo and in vitro PK biographies of the expression used as the test medicine in the study. (12)